Plastik Sanatlar Alanında Resim Sanatçı Seçkileri-2 - Soylu, Rasim; Eren, Abdurrahman; Özgül, Aslıhan; Kalın, Selcan; Şener, Nilgün; Aslan, Simge; Davun, Banu; Öztütüncü, Sabriye; Baykurt, Arif Esen (Akademisyen Yayınevi Kitap DOI Portalı, 2024)
-